The application of Generative Artificial Intelligence (Gen AI) in Nursing Education: A Scoping Review Protocol. - Mooney, Mary; Hardie, Philip; Derwin, Rosemarie; Mc Brien, Barry; Eustace-Cook, Jessica (My University, 2025)
Introduction: This article outlines the protocol for a scoping review that aims to systematically and comprehensively map the available published and unpublished literature on the application of Generative AI as a teaching, learning and assessment strategy in nursing education. Additionally, the protocol seeks to determine the identified ethical considerations it presents, and the measures taken to address them in the nursing educational setting. The scoping review also aims to identify potentially valuable educational practices and practices worthy of further consideration for future research and implementation. Methods and Analysis: To conduct a rigorous and robust scoping review, the review protocol is based on key principles outlined by the Joanna Briggs Institute and Arksey & O' Malley (2005) six-stage iterative framework, as well as the PRISMA-ScR framework guidelines to ensure the transparency of the methodological and reporting approaches to the review. Six databases will be searched: EMBASE (Elsevier), Web of Science Core (Clarivate), CINAHL & Medline (EBSCO), Applied Social Science Index and Abstracts and ERIC (ProQuest). A wide search of supplemental databases and grey literature will also be investigated and reported on. Ethics and dissemination: Ethical review is not required, as scoping reviews are a form of secondary data analysis that synthesises data from publicly available sources. Review findings will be shared with relevant stakeholders and disseminated through a peer-reviewed publication and conference presentations.
PUBLISHED
Keywords: Generative Artificial Intelligence (Gen AI), Nursing Education, Scoping Review, AI Education, Educational Technology; Creative Technologies; Digital Engagement; Clinical learning environment in nursing; Educational Evaluation/Assessment; Health outcomes; Nursing; Nursing Education; Education; Health; Policy